Teacher’s Communication Model in Learning Islamic Education for Autism Children - Mustari Bosra Bosra; Hanif Cahyo Adi; Greget Annisa Syawaliani (Institut Agama Islam Negeri Imam Bonjol Padang, 2020)
The communication model in the education process is the main thing—no exception in education for children who experience psychological difficulties such as children. The material, methods, and learning media needed are supported by a useful communication model to help the progress of religious education for autistic children. This study uses teacher communication methods in learning Islamic Religious Education (PAI). Data collection uses interviews with the support of documentation in the form of photos, videos, and event support during field monitoring. Relevant research results in the study show that the communication model applied in the teaching of Islamic religion in special autistic school children, Bina Anggita Yogyakarta, uses two models: 1 (one) Direction and 2 (two) Directions. One-way communication is used for children whose verbal ability has not yet appeared. While 2-Way communication is used for autistic children who are able to communicate verbally. Strategies in learning use the concept of one teacher, one child. While education is done using the ABA and PECS methods. This method is useful in training and training students in expressing their desires. Based on the findings in this study, the communication model applied in special autism children development schools can be used as a learning model in other schools that manage autistic children.